Каждый за себя: [роман] / Александра Маринина - Маринина Александра Борисовна (Эксмо, 2007)
Экземпляры: (20220406) / Инвентарный номер: 33458 / Цена: 450.12 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 26 / ГРНТИ: 17 / ББК: 84(2=411.2)6